Nonlinear vibration energy harvesting device integrating mechanical stoppers used as synchronous mechanical switches. (September 2014) - Wu, Yipeng; Badel, Adrien; Formosa, Fabien; Liu, Weiqun; Agbossou, Amen
Nonlinear energy extraction techniques for piezoelectric vibration energy harvesting usually require synchronized electronic switches in their electronic interface circuits. But the difficulty to self-power their complex switching control strategies limits their performances, especially in the presence of wideband ambient excitations. This technical note presents a nonlinear energy extraction interface achieved by synchronous mechanical switches. The complex switching control strategy is dodged by taking advantage of mechanical stoppers and the moving part of the piezoelectric oscillator, which is driven by the vibration itself. As a result, the added mechanical stoppers and the self-synchronized nonlinear energy extraction circuit also make the energy harvesting device system be particularly suited to wideband ambient vibrations.